2015
DOI: 10.1182/blood-2014-09-601187
|View full text |Cite
|
Sign up to set email alerts
|

Functions of idh1 and its mutation in the regulation of developmental hematopoiesis in zebrafish

Abstract: Key Points• Zebrafish idh1 plays an important role in the regulation of myelopoiesis and definitive hematopoiesis.• Expression of human IDH1-R132H and its zebrafish orthologue induced an increase in myelopoiesis and 2-hydroxyglutrate.Isocitrate dehydrogenase 1 mutation (IDH1-R132H) was recently identified in acute myeloid leukemia with normal cytogenetics. The mutant enzyme is thought to convert a-ketoglutarate to the pathogenic 2-hydroxyglutarate (2-HG) that affects DNA methylation via inhibition of ten-eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…An increase in 2-hydroxyglutarate (2-HG) level, a reduction of 5-Hydroxymethylcytotsine (5-hmC), and an expansion of myelopoiesis were obtained in these embryos. A human IDH1-R132H–specific inhibitor significantly ameliorated both hematopoietic and 2-HG responses in human but not zebrafish IDH1 mutant expression [63]. This result is not surprising and highlights some of the drawbacks using Zebrafish as a model for human diseases.…”
Section: Zebrafish: Characteristics and Relevance To Human Blood Mmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in 2-hydroxyglutarate (2-HG) level, a reduction of 5-Hydroxymethylcytotsine (5-hmC), and an expansion of myelopoiesis were obtained in these embryos. A human IDH1-R132H–specific inhibitor significantly ameliorated both hematopoietic and 2-HG responses in human but not zebrafish IDH1 mutant expression [63]. This result is not surprising and highlights some of the drawbacks using Zebrafish as a model for human diseases.…”
Section: Zebrafish: Characteristics and Relevance To Human Blood Mmentioning
confidence: 99%
“…These mutations substitute arginine residue almost exclusively at codon 132 in IDH1 (IDH1-R132H) and codons 140 and 172 in IDH2 [62]. To study the involvement of IDH in AML, zidh1 was either suppressed or deleted and resulted in the blockage of differentiation and accumulation of early myeloid progenitor cells, while decreasing macrophage and natural killer progenitor cells [63]. The importance of IDH1 mutation was asserted when plasmids of IDH1-R132H were injected into zebrafish embryos [63].…”
Section: Zebrafish: Characteristics and Relevance To Human Blood Mmentioning
confidence: 99%
See 1 more Smart Citation
“…IDH mutations are found in approximately 30 % of cytogenetically abnormal AML, suggesting a pathogenetic link in leukemia initiation [ 100 , 101 ]. Injection of either human IDH1-R132H or zebrafish idh1 -R146H, a mutant corresponding to human IDH1-R132H, resulted in increased 2-hydroxyglutarate, which in turn induced the expansion of primitive myelopoiesis [ 102 ]. Taken together, these reports suggest that the molecular pathways involved in leukemia are conserved between humans and zebrafish.…”
Section: New Materials For Developmental Biological and Biomedical Smentioning
confidence: 99%
“…AML-associated mutations in IDH1/2 perturb this function, altering the citric acid cycle, and leading to production of the oncometabolite 2-hydroxyglutarate, which alters DNA methylation via inhibition of ten-eleven translocation 2 (TET2) ( 70 , 71 ). When idh1 levels were diminished in zebrafish using morpholino or TALEN approaches, Shi et al observed expansion of pu.1 + precursors, impaired myeloid differentiation and reduced HSC formation ( 72 ). In contrast, when idh2 was diminished, the zebrafish displayed similar myeloid cell defects to idh1 mutants, but normal formation of HSCs, indicating a functional redundancy between the two idh factors during early embryonic HSC formation.…”
Section: Non-fusion Oncogenes In Zebrafish Aml Modelsmentioning
confidence: 99%